2010
DOI: 10.1007/s10545-009-9021-x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐ictal psychosis in adolescent Niemann‐Pick disease type C

Abstract: We describe the presentation of an adolescent with juvenile-onset Niemann-Pick disease type C (NPC) who presented with post-ictal psychosis in the context of a developing seizure disorder. After demonstrating mild gait disturbance beginning at the age of 4 years, he was diagnosed with NPC at age 12 on the basis of 95% of cultured fibroblasts staining positive for filipin and a reduced fibroblast cholesterol esterification rate. He then developed a seizure disorder at age 15, where clusters of seizures produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
10
0
2
Order By: Relevance
“…Imrie et al [4] et Walterfang et al [14,16] décrivent des fratries atteintes par la maladie de NPC [4,25].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Imrie et al [4] et Walterfang et al [14,16] décrivent des fratries atteintes par la maladie de NPC [4,25].…”
Section: Discussionunclassified
“…Des symptômes psychiatriques non spéci-fiques y sont souvent associés (manifestations psychotiques de type schizophrénique, hallucinations visuelles transitoires isolées, syndromes dépressifs, troubles bipolaires, troubles obsessionnels compulsifs, troubles du comportement). Cependant, la maladie de NPC peut également se manifester sous la forme de troubles psychiatriques isolés [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Jusqu'à récemment, la prise en charge était uniquement symptomatique.…”
unclassified
“…200,202,205,208 Postictal psychosis was also reported in NP disease type C, generally limited to a psychotic disorder that follows complex partial or generalized seizure activity, or a cluster of seizures. 209 Frontal lobe atrophy may be prominent in NP disease type C and might be associated with psychosis. 174 Psychosis usually responds to antipsychotic medications, but paradoxical worsening and resistance to antipsychotics can be observed, which might be ameliorated in some cases by using miglustat, a drug that inhibits glycosphingolipid synthesis and the only approved targeted therapy for the disease.…”
Section: Wilson's Diseasementioning
confidence: 99%
“…An initial psychotic disease can sometimes precede the onset of any motor symptoms by up to 10 years. 3 While most, if not all, adult patients show difficulties in vertical gaze (vertical supranuclear ophthalmoplegia) at disease onset, NPC remains heterogeneous in its clinical manifestations and the initial presentation of adult patients may be motor or neuropsychiatric in nature. 9,12 Because of this clinical heterogeneity, adult NPC patients may present to psychiatrists as well as neurologists.…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…62 Neither of these treatments has been trialled in adult NPC patients, although the use of valproic acid for mood disorders has been described in adolescent and adult patients with neuropsychiatric disease. 3,12 Recent data demonstrated that early treatment with sterol-binding agents such as 2-hydroxy-β-cyclodextrin in NPC mice could substantially decrease cholesterol concentrations in the liver and spleen while improving both liver dysfunction and neurodegeneration. 63 Derived from the common spice turmeric, curcumin is a potent antioxidant and may also have positive effects on NPC disease.…”
Section: Treatments In Developmentmentioning
confidence: 99%